An Analysis of Public Trust Level in Performance of Klurak Village Head, Sidoarjo Regency, East Java Province - Santa Wira Kartika Putri Wihendra; Sudarmono Sudarmono (Institut Pemerintahan Dalam Negeri, 2024)
Public trust is a key indicator of trustworthy government and a fundamental characteristic of a well-constructed governance system. The development of the concept begins with the fundamental government led by village head. Therefore, this research aimed to determine the level of confidence possessed by Klurak community regarding village head as well as to assess the impact of performance and the implementation of trustworthy government on public trust. The information was gathered through the use of stratified random sampling and examined using quantitative method and multiple linear regression analysis. The results showed that the level of public trust of Klurak Village placed in village head was 81.9%. This level of trust was impacted by village head performance and trustworthy governance, while other variables influenced 18.1% of the concept. Trustworthy government and village head performance had positive and negative influences on public trust, respectively.